Mapping Analysis of German Language Education Literature Based on Google Scholar and Vosviewer: Bibliometric and Visualization - Hendra, Dani; Achmad, Abdul Kasim (Universitas Negeri Makassar, 2024)
Abstract. This study aims to systematically explore and cluster by mapping and visualizing the german language education research literature. The title and abstract of the article are used to guide the search process by referring to the keyword “german, language, education, german language education”. Found 810 articles that are considered relevant. The study period used as study material is google scholar indexed articles for the last 11 years (2012 to 2022). The results show that research on german language education is separated into 4 terms: german, language, education and german language education with 5 clusters, 2652 links and 9005 total link strength. The term